A Survey of the Perception of Interprofessional Education among Faculty Members of Mazandaran University of Medical Sciences - Leila Shahbaznejad; Seied Ebrahim Mirshah Jafari; Roghayeh Valipour Khajehghyasi (Kerman University of Medical Sciences, 2017)
Background Interprofessional education is an approach aimed at preparing healthcare staff to provide patients with better services in a participatory atmosphere. As such, interprofessional teaching and learning across healthcare professions is very important. Considering the key role of faculty members in advancing the goals of interprofessional education, the present study sought to examine perceptions among faculty members about the concept of interprofessional education. Methods This descriptive cross-sectional study involved faculty members of Mazandaran University of Medical Sciences. The interdisciplinary education perception scale (IEPS) was used to collect information. The data were analyzed using descriptive statistics (frequency, mean and standard deviation) and analytical statistics (t-test, Independent t-test and analysis of variance), and P ≤ 0.05 was considered significant. Results The mean perception score of interprofessional education among faculty members was 3.71 ± 0.44. Although there was no significant difference between the perceptions of female and male faculty members towards interprofessional education (P = 0.104), there was a significant difference between the perception of members of different faculties towards interprofessional education (P = 0.037). In addition, there were significant differences among faculty members in perception towards interprofessional education (P < 0.001) according to their history of educational activity. Conclusions Considering the positive attitude of faculty members towards interprofessional education in the present study, the readiness of students for interprofessional learning in other studies and the positive implications of this educational approach in different areas of health care, it seems that educational planners in the field of medical education must investigate strategies and remove obstacles to implementation of interprofessional education in order to pave the way for its adoption in this domain.